Human population structure - Rosenberg, Noah (Henry Stewart Talks, 2007)
Geographic distribution of genetic variants, Private alleles, Pairwise differences between individuals, Partition of genetic variation, Population structure and inference of ancestry, Decline of heterozygosity with distance from Africa, Serial sampling model for human evolution, Clines and clusters